Chia (Salvia hispanica) harvest residue induces cytokine expression in rabbits - Mónica Ilsy Jiménez-Rojas; Roberto Vázquez-Euán; Héctor Magaña-Sevilla; Gabriel de Jesús Azcorra Perera; Rossana Rodríguez Canul; Roberto Zamora-Bustillos (Ecosistemas y Recursos Agropecuarios, 2018)
The seed of chia plant (Salvia hispanica) is characterized by a high content of polyunsaturated fatty acids, which is an important source of α-linolenic acid for human and animal consumption. During the harvest of the seed, waste is generated that contains remnants of leaves, stems and some seeds, which is generally discarded. The objective of the present work was to evaluate the eect of chia seed residue (CSR) on protein expression of the rabbit immune system, when added as a supplement in the diets of animals deliberately induced to an intestinal infection. Twenty rabbits (New Zealand × California) were randomly distributed in ve treatments and fed ve diets with dierent percentages of CSR inclusion (0, 10, 20, 30 and 40%). Quantication of the relative expression of the anti-inammatory Interleukin-10 (IL-10) and Tumor Necrosis Factor (TNF-α) genes showed that as CSR inclusion levels increased up to 40%, mRNA expression of IL-10 increased signicantly (22.4-fold) with respect to the control, while TNF-α mRNA expression was inversely proportional, where a signicant increase (7.47-fold) in mRNA expression was found in the control group. It is concluded that the indirect inclusion of α-linolenic acid through the consumption of CSR induces a positive response in the immune system of the rabbits and represents an alternative for the formulation of rations with nutraceutical effects.